Interactions of C4 Subtype Metabolic Activities and Transport in Maize Are Revealed through the Characterization of DCT2 Mutants. Issue 2 (26th January 2016) - Weissmann, Sarit; Ma, Fangfang; Furuyama, Koki; Gierse, James; Berg, Howard; Shao, Ying; Taniguchi, Mitsutaka; Allen, Doug K.; Brutnell, Thomas P.
Abstract : C4 photosynthesis includes a complex set of pathways that were analyzed with genetic mutants through molecular and biochemical experiments in maize. Abstract: C4 photosynthesis in grasses requires the coordinated movement of metabolites through two specialized leaf cell types, mesophyll (M ) and bundle sheath (BS ), to concentrate CO2 around Rubisco. Despite the importance of transporters in this process, few have been identified or rigorously characterized. In maize ( Zea mays ), DCT2 has been proposed to function as a plastid-localized malate transporter and is preferentially expressed in BS cells. Here, we characterized the role of DCT2 in maize leaves using Activator -tagged mutant alleles. Our results indicate that DCT2 enables the transport of malate into the BS chloroplast. Isotopic labeling experiments show that the loss of DCT2 results in markedly different metabolic network operation and dramatically reduced biomass production. In the absence of a functioning malate shuttle, dct2 lines survive through the enhanced use of the phosphoenolpyruvate carboxykinase carbon shuttle pathway that in wild-type maize accounts for ∼25% of the photosynthetic activity. The results emphasize the importance of malate transport during C4 photosynthesis, define the role of a primary malate transporter in BS cells, and support a model for carbon exchange between BS and M cells in maize.